Algunos vocablos del léxico capilar en el español de México : Octavio Cano Silva, Ioana Alexandrescu - Cano Silva, Octavio; Alexandrescu, Ioana (Acta Hispanica, 2014)
Our paper deals with some wordsbelonging to the hair-related vocabulary inMexican Spanish. It aims to track these wordsin five recent dictionaries of Spanish, in orderto achieve a panoramic view on two issues:their coverage and the way they are dealt within these dictionaries. The five dictionariescompared are the following: Diccionario delespañol de México, Diccionario de la lengua españolaby the Real Academia Española, Diccionarioescolar, Diccionario de mexicanismos y Diccionarioacadémico de americanismos. The methodologicalcontribution of our paper lies on the fact that itputs on the same level these dictionaries, whilethe point of comparison usually is the RealAcademia Española's dictionary, and its culturalone is given by the attempt to retrieve wordsthat are very common and widely used inMexican Spanish but lack lexicographicalregistration.